2009
DOI: 10.1155/2009/217469
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interaction between Gold Nanoparticles and Multiwalled Carbon Nanotubes via an Intermediatory

Abstract: A new and effective method has been developed where self-assembled gold nanoparticles (Au-NPs) of ∼10 nm diameter are successfully attached onto the surface of sidewalls and ends of thiol-terminated multi-walled carbon nanotubes (MWNTs) functionalized with orthomercaptoaniline, acting as a bridging agent. It can bridge the carbon nanotubes (CNTs) and Au-NPs via the bi-functional moiety with benzene unit at one end and thiol group at the other end by self-assembly. The ortho-mercaptoaniline was first grafted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The diffraction pattern in Figure 4 curve b is in good agreement with face-centered cubic structure of metallic gold (JCPDS: 04-0784) [25,44].The peaks at 38.17, 44.28, 64.61and 77.72° are assigned to facecentered cubic bulk Au (111), (200), (220) and (311), respectively [45,46]. The crystallite size is calculated by Debye-Scherrer formula [47]: D = Kλ/βcosθ, where D is the particle size, K is the Scherrer constant (shape factor), λ is the wavelength of the X-ray, β is the full width half maximum (FWHM), θ is the Braggle angle.…”
Section: Xrd Measurementsupporting
confidence: 67%
“…The diffraction pattern in Figure 4 curve b is in good agreement with face-centered cubic structure of metallic gold (JCPDS: 04-0784) [25,44].The peaks at 38.17, 44.28, 64.61and 77.72° are assigned to facecentered cubic bulk Au (111), (200), (220) and (311), respectively [45,46]. The crystallite size is calculated by Debye-Scherrer formula [47]: D = Kλ/βcosθ, where D is the particle size, K is the Scherrer constant (shape factor), λ is the wavelength of the X-ray, β is the full width half maximum (FWHM), θ is the Braggle angle.…”
Section: Xrd Measurementsupporting
confidence: 67%
“…Caps were made of gold nanoparticles (GNPs) functionalised with alkanethiols in order to tune their size and surface properties. It has been demonstrated that alkanethiols readily assemble as a monolayer on the surface of gold [14], [15], [16], [17], [18], [19], [20], [21], [22], which is facilitated by strong bonds between gold and sulphur, and readily formed under ambient conditions. In addition, GNPs can be detected quite easily under the Transmission Electron Microscope (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…Both spectra show the characteristic π plasmon band of SWNTs at ~270 nm [43]. The SWCNT spectrum shows very weak bands at ~700 nm and 750 nm that correspond to the electronic transitions between the Van Hove singularities in the nanotube density of states, in these cases the E 11 transitions for metallic arc discharge nanotubes [44] (see inset)…”
Section: Materials Characterisationsmentioning
confidence: 96%
“…The Au/SWCNT shows an additional clear broad absorption band at ~560 nm which corresponds to a Au surface plasmon resonance band [44] and is characteristic of suspended Au particle sizes of ≤15nm [45]. In the spectrum of the composite material, the π plasmon band is somewhat dampened and red shifted by the presence of the Au nanoparticles.…”
Section: Materials Characterisationsmentioning
confidence: 99%